Effect of over-2-year dual antiplatelet therapy on the rate of major adverse cardiac and cerebral events for everolimus-eluting stent implantation: The landmark analysis from Tokyo-MD PCI registry. Issue 6 (June 2017) - Ueshima, Daisuke; Ashikaga, Takashi; Yoshikawa, Shunji; Sasaoka, Taro; Hatano, Yu; Kurihara, Ken; Maejima, Yasuhiro; Isobe, Mitsuaki
Abstract: Background: Long-term dual antiplatelet therapy (DAPT) for patients treated with coronary stents has been reported to be effective. However the effectiveness of long-term DAPT for everolimus-eluting stent (EES) implanted patients has been controversial. We assessed the major adverse cardiac and cerebral events (MACCE: a composite of death, myocardial infarction, or cerebral arterial disease) in patients free from MACCE during the first 2 years after EES implantation. Methods and results: A total of 1918 patients who underwent successful percutaneous coronary intervention (PCI) with EES at 22 centers in Japan in 2010–2011 were enrolled, and 742 patients were free from MACCE for 2 years. We divided these MACCE-free patients into two groups: those who received DAPT for >2 years (Over-2-Year DAPT: n = 591), and those who received DAPT for ≤2 years (Under-2-Year DAPT: n = 151). We performed the landmark analysis that began at 2 years and evaluated at 3 years after PCI about the occurrence of MACCE, major bleeding, stent thrombosis, and restenosis between these groups, both with and without baseline adjustment by propensity score matching ( n = 145 in both groups). Results: Fifty MACCE cases were reported (Over-2-Year DAPT, 38; Under-2-Year DAPT, 12), with no significant differences between the 2 groups (log-rank test, p = 0.19). Even after baseline adjustment, there were no differences in MACCE occurrence (Over-2-Year DAPT, 8; Under-2-Year DAPT, 11, p = 0.19); 15 cases of major bleeding, 5 of restenosis, and 2 of stent thrombosis were observed after 2-years' follow-up, with no statistical differences between the groups, although the event numbers were too low for comparison. Conclusion: Continuing DAPT for >2 years did not prevent MACCE in patients free from MACCE during initial 2 years after EES implantation. Few events of major bleeding, stent thrombosis, and restenosis were observed, with no statistical differences.